INTERPRETIVE STRUCTURAL MODELLING FAKTOR FAKTOR YANG MEMPENGHARUHI KEPATUHAN WAJIB PAJAK UMKM DI KOTA MEDAN - Junawan Junawan; Sumardi Adiman (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
The purpose of this study was to determine the factors that influence MSME tax compliance by using interpretive structural modeling methods. Based on the literature review that has been given to tax experts and MSME actors, four factors studied were identified to explain MSME taxpayer compliance, namely: Knowledge and Understanding of Taxes, Taxpayer Trust Levels, Willingness to Pay Taxes, and Awareness of Paying Taxes. Results of the structural modeling method The interpretive shows that Tax Knowledge and Understanding, Taxpayer Trust Level are the most influencing factors in MSME taxpayer compliance, and the next level that will be pushed is the willingness and awareness to pay taxes especially in Medan City.